PP111 The Use Of Long-acting Injectable Antipsychotics In Schizophrenia. (12th January 2018) - Mennini, Francesco; Marcellusi, Andrea; Verzura, Claudio; Trovini, Giada; Rapinesi, Chiara; Kotzalidis, Georgios D.; De Filippis, Sergio; Carrus, Dario; Ballerini, Andrea; Francomano, Antonio; Ducci, Giuseppe; Del Casale, Antonio; et al.
Abstract : INTRODUCTION: Schizophrenia is a severe mental disease that affects approximately 1 percent of the population with a relevant chronic impact on social and occupational functioning, and daily activities. The aim of this analysis was to evaluate the clinical and economic consequences of long-acting injectable (LAI) treatment in patients with psychotic disorders, with a special focus on schizophrenia, in Italian real world practice. METHODS: A retrospective, observational mirror-study was developed to analyze outcomes measure referred to patients with psychotic disorders. Five hospital centers were involved in this study that collected patient level data from clinical databases. Retrospective data for each patient were referred to 6 months before LAI drug administration and 6 months after. A paired-Samples t-test was performed in order to identify statistical differences between pre- and post-LAI administration. RESULTS: A total number of 308 patients were enrolled in the study (65.6 percent male). Of these 221 were eligible for our analysis (119 with schizophrenia). In the six months after LAI administration period we estimate a 47.3 percent reduction of the antipsychotic drugs (43.8 percent for schizophrenic patients), 94.7 percent reduction of hospitalizations (94.0 percent for schizophrenic patients) and adherent patients increase to 198/221 patients (78/221 in pre-LAI administration period). All differences between pre- and post- LAI administration period were statistically significant with a p< .005. In Italy over 152 thousand schizophrenic treated patients were estimated. Assuming that 20–40 percent of patients are eligible to the Mo.Ma (Model of Management) approach, our model estimates a direct cost reduction during the first year of implementation of around EUR12 million. Additionally, EUR18 million of direct costs in the mid-term and EUR58 million of indirect costs could be saved in the mid-term estimating a total cost reduction, due to the Mo.Ma approach, of about EUR90 million. CONCLUSIONS: This new therapeutic approach could change the cost structure of schizophrenia by decreasing costs with efficient economic resource allocation guaranteed from efficient diagnostic and therapeutic pathways.